A Penta-band Antenna using Symmetrical DGS for RF Energy Harvesting in IoT Applications - Thanh, Tu Duong Thi; Quan, Pham Duy; Huu Phuc, Phan; Thao, Hoang Thi Phuong (Engineering, Technology & Applied Science Research, 2025)
The Radiofrequency (RF) energy harvesting technology offers sustainable and non-maintenance power for wireless sensor networks, Internet of Things (IoT) devices, and low-power electronics. Its ongoing advances in improving efficiency are miniaturizing rectennas and making multiple-band antennas capture versatile and efficient electromagnetic radiation across various frequency bands. This paper uses a composed structure of three rings, a symmetrical Defected Ground Structure (DGS), and a shorting pin to construct a penta-band antenna. The antenna operates at 2.4 GHz, 5 GHz, 6 GHz, 7.4 GHz, and 8.7 GHz, with a wide bandwidth of 747 MHz, 286 MHz, 397 MHz, 760 MHz, and 1773 MHz, respectively. Thus, the proposed antenna can capture energy from diverse RF sources such as the IEEE 802.11be standard (WiFi-7), C-band satellite, and radar communications. Furthermore, the proposed antenna achieves a good gain of 2.31 dBi, 4.56 dBi, 4.16 dBi, 5.46 dBi, and 5.41 dBi at resonant frequencies of 2.4, 5, 6, 7.4, and 8.7 GHz, respectively, and a high radiation efficiency of over 90%. Based on the Fire Retardant 4 (FR4) substrate, the eventual size of the antenna is 41.5×37×1.6 mm, which is relatively compact for RF energy harvesting in IoT.